Implementasi Kebijakan Dana Desa (DD) Di Desa Parbubu Ii Kecamatan Tarutung Kabupaten Tapanuli Utara - Ivan Simorangkir; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The method used is descriptive method with a qualitative approach. Data collection techniques were carried out by interviews, observation and documentation related to the implementation of village fund policies (DD) in Parbubu II Village, Tarutung District, North Tapanuli Regency. Data based on findings by the author to describe ongoing policy phenomena based on finding data using Marilee S Grindle's theory which states that the task of implementation is to form a link that makes it easier for policy objectives to be realized as a result of a village government activity. In implementing the Village Fund (DD) policy, it must be implemented as a development ball policy. Meanwhile, the implementation of instructions is not only acceptable but must also be clear. Meanwhile, if the indicators used for the positive and negative aspects of the Village Fund (DD) policy are linked to so many policy issues in Parbubu II village as data analyzed by researchers regarding village fund policies (DD) in Parbubu II Village, Tarutung District, North Tapanuli Regency.